ADSORPTION OF GIBBERELLIC ACID ONTO NATURAL KAOLIN FROM TATAKAN, SOUTH KALIMANTAN - Sunardi Sunardi; Yateman Arryanto; Sutarno Sutarno (Universitas Gadjah Mada, 2009)
Adsorption of gibberellic acid (GA3) onto raw and purified kaolin from Tatakan, South Kalimantan was investigated in this study. Purification process was done by sedimentation to obtain relative pure kaolinite. Raw and purified kaolin samples were characterized by Fourier transformed infrared (FTIR) spectroscopy and X-ray diffractometer (XRD). The adsorption process was carried out in a batch system and the effect of pH, contact time and GA3 concentration were experimentally studied to evaluate the adsorption capacity. The amount of GA3 adsorbed was determined by UV spectrophotometer. The result showed that the raw kaolin from South Kalimantan consist of 53.36% kaolinite, 29.47% halloysite, 4.47% chlorite, 11.32% quartz and 1.38% christobalite and the purified kaolin consist of 73.03% kaolinite, 22.6% halloysite, 0.77% chlorite, 1.37% quartz and 2.23% christobalite Adsorption experimental indicate that the optimum adsorption took place at pH 7 and contact time for 4 h. Adsorption of GA3 was described by the Langmuir adsorption isotherm model with adsorption capacity of 8.91 mg/g on raw kaolin and 10.38 mg/g on purified kaolin.